« L’IDENTITE DU CHABIN, LE PARLER CREOLE ET L’INSCRIPTION D’UNE SOCIETE CARIBEENNE CREOLISEE DANS RAVINES DU DEVANT-JOUR DE RAPHAËL CONFIANT » - Baba Abraham Jatoe-Kaleo (European Scientific Journal, ESJ, 2013)
In order to retrieve its rightful place in the linguistic map of the Caribbean Islands, Creole […] much as is with the Chabin and Sonson, must take on a “ferocity” in the face of the dominant French language, and deal “two or three scintillating blows at the latter” in order to take from it “its title” of dominant language on the language map of the Caribbean. Creole is inscribed therefore, in the text, through words constructed in diverse ways from the addition of prefixes and suffixes to French words, by the use of outmoded French words retrieved from the Middle Ages, and through the use of words from African, Indian… and other doubtful sources.